Control system for modern house - Mohd Hafizuddin, Hasnan (2009)
For more and more people, a control system has become a necessary part of their home and they wouldn't dream of living in a home without one. This trend can be directly traced from the life style and daily routine which is always busy with works. People nowadays always want something that can make their life easier. This project is proposed because it is believed that this project can make people life easier. This project is also quite interesting as it combines a lot of features such as lighting control module, mail notification module and door locking system. More important of this project is low cost. The basic idea for lighting control is when low light intensity occurs, the control circuit will turn on the light automatically. For mail notification, the basic idea is when owner received a new mail, the control circuit will play the voice message. Last but not least, the basic idea for door locking system is when owner want to go out and into the house, the door will open and close automatically.